Lithium iron phosphate coated lithium-rich manganese-based material, and preparation method and application thereof

CN117954601BActive Publication Date: 2026-11-03GUANGDONG BRUNP RECYCLING TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410115916.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-26
Publication Date
2026-11-03
Estimated Expiration
2044-01-26

AI Technical Summary

Technical Problem

Existing lithium iron phosphate and lithium-rich manganese-based materials suffer from problems such as low lithium-ion diffusion rate, poor electronic conductivity, poor cycle performance, and severe voltage drop in lithium-ion batteries, which affect their rate performance and stability.

Method used

Lithium iron phosphate was coated onto the surface of lithium-rich manganese-based materials using a solvothermal method. Thioacetamide was introduced during the reaction to form a sulfide layer and anion doping, which improved the conductivity and crystal structure of the material and enhanced lithium-ion diffusion.

Benefits of technology

It achieves high capacity and high stability of lithium-ion batteries, improves the cycle performance and rate performance of lithium-ion batteries, and simplifies the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117954601B_ABST
    Figure CN117954601B_ABST
Patent Text Reader

Abstract

The present disclosure provides a lithium phosphate coated lithium-rich manganese-based material, a preparation method and application thereof, and belongs to the technical field of positive electrode materials. The lithium phosphate coated lithium-rich manganese-based material provided by the present disclosure coats lithium phosphate on the surface of the lithium-rich manganese-based material by a solvothermal method, and introduces thioacetamide during preparation for modification, thereby obtaining a lithium phosphate coated lithium-rich manganese-based material with high capacity and high stability. When the lithium phosphate coated lithium-rich manganese-based material is applied to the preparation of a lithium ion battery, the lithium ion battery prepared has excellent cycle performance and rate performance. Meanwhile, the preparation method provided by the present disclosure is simple to operate and is conducive to actual production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure belongs to the field of cathode material technology, and particularly relates to a lithium iron phosphate coated lithium-rich manganese-based material, its preparation method and application. Background Technology

[0002] The most commonly used cathode materials in lithium-ion batteries are lithium iron phosphate (LFP) and ternary materials. LFP, with its advantages of low cost, good high-temperature performance, large capacity, no memory effect, light weight, and environmental friendliness, has become a highly promising cathode material for lithium-ion batteries. However, it also suffers from several drawbacks that severely hinder its further development, such as relatively low lithium-ion diffusion rate and electronic conductivity. In addition, lithium-rich manganese-based materials with high reversible specific capacity have also attracted widespread attention. These materials offer numerous advantages, including high specific capacity, low cost, and environmental friendliness. However, they also exhibit some fatal flaws, such as poor cycle performance, poor rate performance, poor conductivity, and severe voltage drop. Therefore, improving the rate performance and cycle stability of lithium-rich manganese-based cathode materials has become a key research focus in recent years. Summary of the Invention

[0003] The purpose of this disclosure is to overcome the shortcomings of the prior art and provide a lithium iron phosphate coated lithium-rich manganese-based material, its preparation method and application, which can achieve excellent rate performance and cycle performance of lithium-ion batteries.

[0004] To achieve the above objectives, in a first aspect of this disclosure, a method for preparing lithium iron phosphate-coated lithium-rich manganese-based materials is provided, the method comprising the following steps:

[0005] Iron source, phosphorus source and lithium-rich manganese-based material are dissolved in a first organic solvent to obtain a first mixed solution;

[0006] The lithium source is dissolved in the second organic solvent to obtain the second mixed solution;

[0007] The second mixed solution is added dropwise to the first mixed solution and stirred to obtain the third mixed solution;

[0008] Thioacetamide was added to the third mixed solution and heated to react. After the reaction was completed, the solution was cooled, filtered, and the filter residue was collected, washed, and dried to obtain a lithium iron phosphate-coated lithium-rich manganese-based material precursor.

[0009] The lithium iron phosphate-coated lithium-rich manganese-based material precursor was ground and then calcined to obtain the lithium iron phosphate-coated lithium-rich manganese-based material.

[0010] The method for preparing lithium iron phosphate coated lithium-rich manganese-based materials disclosed herein uses a solvothermal method to coat lithium iron phosphate onto the surface of lithium-rich manganese-based materials, forming a uniform coating shell. This overcomes the poor cycle performance of lithium-rich manganese-based materials, resulting in lithium iron phosphate coated lithium-rich manganese-based materials with both high capacity and stability, thereby improving the rate performance and cycle performance of lithium-ion batteries prepared using them.

[0011] Specifically, this disclosure introduces thioacetamide during the preparation process. The introduction of thioacetamide can modify the lithium-rich manganese-based core layer and the lithium iron phosphate shell layer to a certain extent. On the one hand, thioacetamide can undergo a sulfidation reaction with transition metal ions in the lithium-rich manganese-based core material, forming a thin layer of sulfide (MnS, NiS2) on the surface. This sulfide layer can prevent further reaction between external sulfur and internal transition metals. Furthermore, due to the small size of the transition metal cations, their outward diffusion rate is faster, so the sulfidation reaction mainly occurs on the surface. The thin layer of sulfide formed on the surface of the lithium-rich manganese-based material can improve the conductivity of the material. On the other hand, thioacetamide can act as an anion dopant in the synthesis of lithium phosphate. The S in thioacetamide can partially replace O, performing anion doping at the O site. 2- The ionic radius is greater than O 2- The ionic radius of S is such that S doping into the LiFePO4 matrix can expand the lattice, which helps lithium ions migrate in the diffusion channel; therefore, the addition of thioacetamide can prevent the generation of impurity FeS2. By adding thioacetamide and reacting with the two materials in the core and shell, the electrochemical performance of the cathode material is synergistically improved.

[0012] In one embodiment, the mass ratio of the thioacetamide to the lithium-rich manganese-based material is (0.02-0.04):1.

[0013] For example, the mass ratio of the thioacetamide to the lithium-rich manganese-based material can be 0.02:1, 0.022:1, 0.024:1, 0.026:1, 0.028:1, 0.03:1, 0.032:1, 0.034:1, 0.036:1, 0.038:1, or 0.04:1.

[0014] This disclosure reveals that when the mass ratio of thioacetamide to lithium-rich manganese-based material is (0.02-0.04):1, a thin layer of sulfide with moderate and uniform thickness can be generated on the surface of the lithium-rich manganese-based material, thereby improving the conductivity of lithium iron phosphate coated lithium-rich manganese-based material and thus making the prepared lithium-ion battery have better overall performance.

[0015] In one embodiment, the molar ratio of sulfur in the thioacetamide to iron in the iron source is (0.02-0.3):1.

[0016] For example, the molar ratio of sulfur in the thioacetamide to iron in the iron source can be 0.02:1, 0.05:1, 0.08:1, 0.1:1, 0.12:1, 0.15:1, 0.18:1, 0.2:1, 0.22:1, 0.24:1, 0.26:1, 0.28:1, or 0.3:1.

[0017] This disclosure reveals that when the molar ratio of thioacetamide to iron in the iron source is further selected to be in the range of (0.02-0.3):1, it can play a good role in anion doping when generating lithium iron phosphate materials, thereby expanding the crystal lattice, which helps the migration of lithium ions in the diffusion channel, and thus improves the electrochemical performance of the lithium-ion battery prepared subsequently.

[0018] In one embodiment, the molar ratio of iron in the iron source, phosphorus in the phosphorus source, and lithium in the lithium source is 1:1:1.

[0019] This disclosure reveals that the molar ratio of iron in the iron source, phosphorus in the phosphorus source, and lithium in the lithium source has a certain impact on the electrochemical performance of lithium-ion batteries. When the molar ratio of iron in the iron source, phosphorus in the phosphorus source, and lithium in the lithium source is selected as 1:1:1, the introduced thioacetamide can effectively expand the crystal lattice, thereby achieving excellent cycle stability and rate performance of lithium-ion batteries.

[0020] In one embodiment, the mass concentration of the solute in the first mixed solution is (0.08-0.18) g / mL.

[0021] In one embodiment, the mass concentration of the solute in the second mixed solution is (0.008-0.028) g / mL.

[0022] This disclosure reveals that when the mass concentrations of the solute in the first and second mixed solutions are within the aforementioned ranges, the solute mass concentrations are moderate. This avoids the addition of excessive organic solvents while ensuring dissolution, improves production efficiency, and helps form a core-shell structure product with a more uniform coating, thereby achieving good overall performance.

[0023] In one embodiment, the first organic solvent and the second organic solvent are each independently selected from at least one of ethylene glycol, glycerol, or ethanol.

[0024] This study found that dissolving and reacting with organic solvents containing hydroxyl groups can help thioacetamide better modify lithium-rich manganese-based materials and lithium iron phosphate materials, thereby achieving better overall performance of lithium-ion batteries.

[0025] In one embodiment, at least one of the following (a)-(c):

[0026] (a) The iron source is selected from at least one of ferrous phosphate, ferrous oxalate, ferrous sulfate or ferrous chloride;

[0027] (b) The phosphorus source is selected from at least one of ammonium dihydrogen phosphate, ammonium phosphate, diammonium hydrogen phosphate, and potassium dihydrogen phosphate;

[0028] (c) The lithium source is selected from at least one of lithium carbonate, lithium hydroxide or lithium acetate.

[0029] In one embodiment, the structural formula of the lithium-rich manganese-based material is: xLi2MnO3·(1-x)LiNiO2, where 0.3 < x < 1.

[0030] The lithium-rich manganese-based material disclosed herein can be manufactured in-house or purchased commercially.

[0031] In one embodiment, the preparation method of lithium-rich manganese-based material includes the following steps:

[0032] Manganese sulfate and sodium carbonate were dissolved in an organic solvent, then heated and kept at a constant temperature to react. After the reaction was completed, the mixture was cooled, filtered, and the residue was collected and dried. After drying, the residue was calcined for the first time to obtain the manganese dioxide precursor.

[0033] Manganese dioxide precursor, nickel sulfate and lithium hydroxide were added to an organic solvent and stirred to form a suspension. The suspension was dried and the solid was calcined to obtain lithium-rich manganese-based material (LNMO).

[0034] In one embodiment, in the method for preparing the lithium-rich manganese-based material, the molar ratio of manganese sulfate to sodium carbonate is 1:1.

[0035] In one embodiment, in the preparation method of the lithium-rich manganese-based material, the molar ratio of lithium in lithium hydroxide, manganese in the manganese dioxide precursor, and nickel in nickel sulfate is 1.25:0.6:0.2.

[0036] In one embodiment, in the preparation method of the lithium-rich manganese-based material, the temperature of the heat preservation reaction is 185-195℃, and the heat preservation reaction time is 11-13h.

[0037] In one embodiment, in the preparation method of the lithium-rich manganese-based material, the first calcination temperature is 380-420℃, the first calcination time is 5-12h, and the first calcination atmosphere is an air atmosphere.

[0038] In one embodiment, the stirring time in the preparation method of the lithium-rich manganese-based material is 0.5-1.5 h.

[0039] In one embodiment, in the preparation method of the lithium-rich manganese-based material, the temperature for drying the suspension is 45-55°C and the time is 45-50 hours.

[0040] In one embodiment, in the preparation method of the lithium-rich manganese-based material, the second calcination temperature is 800-900℃, the second calcination time is 6-10h, and the second calcination atmosphere is an air atmosphere.

[0041] In one embodiment, the organic solvent in the preparation method of the lithium-rich manganese-based material is ethanol.

[0042] In one embodiment, the dropping rate of the second mixed solution into the first mixed solution is 25-50 mL / h.

[0043] In one embodiment, the stirring time is 0.5-1.5 hours.

[0044] This disclosure reveals that adding the second mixed solution dropwise to the first mixed solution and stirring for 0.5-1.5 hours ensures thorough mixing and initial reaction of the two solutions, forming a uniform coating layer.

[0045] In one embodiment, the heating reaction temperature is 150-210°C, and the heating reaction time is 8-12 hours.

[0046] This disclosure reveals that when the temperature and time of the heating reaction are within the range given in this disclosure, the lithium iron phosphate generated by the reaction can be uniformly coated on the surface of the lithium-rich manganese-based material through a solvothermal method, forming a uniform shell structure; thereby improving the overall performance of the prepared lithium-ion battery.

[0047] In one embodiment, the calcination temperature is 450-550°C and the calcination time is 2.5-3.5 h.

[0048] In one embodiment, the calcination atmosphere is an inert atmosphere, which is nitrogen or a rare gas.

[0049] This study found that the calcination temperature, time, and atmosphere, within the range given in this publication, can help achieve high capacity and high stability of lithium iron phosphate coated lithium-rich manganese-based materials, thereby helping to achieve good cycle performance and rate performance of lithium-ion batteries.

[0050] In one embodiment, the washing process involves sequentially washing with deionized water and ethanol.

[0051] In one embodiment, the drying is performed under vacuum at 65-75°C for 2.5-3.5 hours.

[0052] In a second aspect, this disclosure provides a lithium iron phosphate coated lithium-rich manganese-based material, wherein the lithium iron phosphate coated lithium-rich manganese-based material is prepared using the preparation method described in this disclosure.

[0053] The lithium iron phosphate-coated lithium-rich manganese-based material disclosed herein has a spherical core-shell structure, and the core and shell structures are modified accordingly with thioacetamide, exhibiting high capacity and high stability. When applied to the subsequent preparation of lithium-ion batteries, the resulting lithium-ion batteries have excellent cycle performance and rate performance.

[0054] In a third aspect of this disclosure, the application of the lithium iron phosphate-coated lithium-rich manganese-based material in the preparation of cathode materials is provided.

[0055] In a fourth aspect, this disclosure provides a lithium-ion battery, including a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode comprises the lithium iron phosphate coated lithium-rich manganese-based material described in this disclosure.

[0056] In one embodiment, the positive electrode sheet comprises the following raw materials: lithium iron phosphate coated lithium-rich manganese-based material, conductive agent, and adhesive.

[0057] In one embodiment, the mass ratio of the lithium iron phosphate coated lithium-rich manganese-based material, the conductive agent, and the adhesive is 90:5:5.

[0058] In one embodiment, the conductive agent is acetylene black, and the adhesive is polyvinylidene fluoride.

[0059] In one embodiment, the positive electrode sheet is prepared by: adding lithium iron phosphate coated lithium-rich manganese-based material, conductive agent and adhesive into N-methylpyrrolidone, mixing evenly, coating onto aluminum foil, and then drying, assembling and pressing to obtain the positive electrode sheet.

[0060] In one embodiment, the negative electrode is lithium metal.

[0061] In one embodiment, the electrolyte is a solution of lithium hexafluorophosphate in ethylene carbonate (EC) and dimethyl carbonate (DMC).

[0062] Compared with the prior art, the beneficial effects of this disclosure are as follows:

[0063] The method for preparing lithium iron phosphate-coated lithium-rich manganese-based materials disclosed in this disclosure involves coating the surface of the lithium iron phosphate material with lithium iron phosphate via a solvothermal process. During the reaction, thioacetamide is introduced to modify both the lithium iron phosphate layer and the lithium-rich manganese base layer, resulting in a lithium iron phosphate-coated lithium-rich manganese-based material with both high capacity and high stability. When applied to the preparation of lithium-ion batteries, the resulting lithium-ion batteries exhibit excellent cycle performance and rate capability. Furthermore, the preparation method provided in this disclosure is simple to operate and beneficial for practical production. Attached Figure Description

[0064] Figure 1The image shows a SEM image of the lithium iron phosphate-coated lithium-rich manganese-based material prepared in Example 1. Detailed Implementation

[0065] To better illustrate the purpose, technical solutions, and advantages of this disclosure, the following will provide further explanation of this disclosure in conjunction with specific embodiments.

[0066] Unless otherwise specified, the reagents, methods and equipment used in this disclosure are all conventional reagents, methods and equipment in the art.

[0067] The lithium-rich manganese-based materials used in the embodiments and comparative examples of this disclosure are self-made, and the self-made method includes the following steps:

[0068] (1) Weigh a certain amount of MnSO4 and Na2CO3 in a 1:1 molar ratio, dissolve them in 80 mL of ethanol and stir until homogeneous to obtain a mixed solution; (the concentrations of MnSO4 and Na2CO3 are both 1 mol / L).

[0069] (2) The mixed solution was transferred to a 100 mL reaction vessel, heated to 190 °C and kept at the temperature for 12 h to prepare MnCO3; after the reaction was completed, it was naturally cooled to room temperature, the sample was collected and dried, and then calcined at 400 °C in air atmosphere for 8 h to obtain MnO2 precursor.

[0070] (3) Add MnO2 precursor, NiSO4 and LiOH to ethanol (the total mass of manganese dioxide precursor, NiSO4 and LiOH to the volume ratio of ethanol is 0.1g:1mL, and the molar ratio of lithium in LiOH, manganese in MnO2 precursor and nickel in NiSO4 is Li:Mn:Ni = 1.25:0.6:0.2), stir for 1h to form a suspension, then dry the suspension at 50℃ for 48 hours, filter, collect the filter residue and calcine at 850℃ for 8 hours to obtain lithium-rich manganese-based material (LNMO).

[0071] Example 1

[0072] This disclosure provides a lithium iron phosphate-coated lithium-rich manganese-based material, the preparation method of which includes the following steps:

[0073] (1) Weigh out FeSO4·7H2O (1.67g, 6mmol), H3PO4 (0.59g, 6mmol), and 0.3g LNMO and dissolve them in 20mL of ethylene glycol to obtain the first mixed solution;

[0074] (2) Weigh out 0.25 g of LiOH·H2O and dissolve it in 15 mL of ethylene glycol to obtain a second mixed solution;

[0075] (3) The second mixed solution is added dropwise to the first mixed solution at a rate of 35 mL / h and stirred. After the addition is completed, the mixture is stirred for 1 h to obtain the third mixed solution. The molar ratio of lithium in LiOH·H2O, iron in FeSO4·7H2O and phosphorus in H3PO4 is: Li∶Fe∶P=1∶1∶1.

[0076] (4) Add thioacetamide (0.009 g, 0.12 mmol) to the third mixed solution (the molar ratio of sulfur in thioacetamide to iron in the iron source is: S:Fe = 0.02:1, and the mass ratio of thioacetamide to LNMO is 3 wt%). After the addition is complete, transfer the solution to a 100 mL reactor and react at 180 °C for 10 h. After the reaction is complete, cool naturally to room temperature, filter, collect the filter residue, wash with deionized water and ethanol three times, and after washing, vacuum dry at 70 °C for 3 h to obtain lithium iron phosphate coated lithium-rich manganese-based material precursor.

[0077] (5) The lithium iron phosphate coated lithium-rich manganese-based material precursor was ground and calcined at 500°C for 3 hours under an argon atmosphere to obtain lithium iron phosphate coated lithium-rich manganese-based material.

[0078] SEM images of the prepared lithium iron phosphate coated lithium-rich manganese-based material are shown below. Figure 1 As shown in the figure, the prepared lithium iron phosphate coated lithium-rich manganese-based material is a regular spherical material with uniform particle size distribution.

[0079] Example 2

[0080] This disclosure provides a lithium iron phosphate coated lithium-rich manganese-based material. The only difference between the lithium iron phosphate coated lithium-rich manganese-based material and Example 1 is that the molar ratio of sulfur in thioacetamide to iron in the iron source is S:Fe = 0.1:1.

[0081] Example 3

[0082] This disclosure provides a lithium iron phosphate coated lithium-rich manganese-based material. The only difference between the lithium iron phosphate coated lithium-rich manganese-based material and Example 1 is that the molar ratio of sulfur in thioacetamide to iron in the iron source is S:Fe = 0.2:1.

[0083] Example 4

[0084] This disclosure provides a lithium iron phosphate coated lithium-rich manganese-based material. The only difference between the lithium iron phosphate coated lithium-rich manganese-based material and Example 1 is that the molar ratio of sulfur in thioacetamide to iron in the iron source is S:Fe = 0.3:1.

[0085] Example 5

[0086] This disclosure provides a lithium iron phosphate coated lithium-rich manganese-based material. The only difference between the lithium iron phosphate coated lithium-rich manganese-based material and Example 1 is that the molar ratio of sulfur in thioacetamide to iron in the iron source is S:Fe = 0.01:1.

[0087] Example 6

[0088] This disclosure provides a lithium iron phosphate coated lithium-rich manganese-based material. The only difference between the lithium iron phosphate coated lithium-rich manganese-based material and Example 1 is that the molar ratio of sulfur in thioacetamide to iron in the iron source is S:Fe = 0.4:1.

[0089] Example 7

[0090] This disclosure provides a lithium iron phosphate coated lithium-rich manganese-based material, the only difference between the lithium iron phosphate coated lithium-rich manganese-based material and Example 1 is that the mass ratio of thioacetamide to LNMO is 4 wt%.

[0091] Example 8

[0092] This disclosure provides a lithium iron phosphate coated lithium-rich manganese-based material, the only difference between the lithium iron phosphate coated lithium-rich manganese-based material and Example 1 is that the mass ratio of thioacetamide to LNMO is 1 wt%.

[0093] Example 9

[0094] This disclosure provides a lithium iron phosphate coated lithium-rich manganese-based material, the only difference between the lithium iron phosphate coated lithium-rich manganese-based material and Example 1 is that the mass ratio of thioacetamide to LNMO is 6 wt%.

[0095] Example 10

[0096] This disclosure provides a lithium iron phosphate coated lithium-rich manganese-based material, the only difference between the lithium iron phosphate coated lithium-rich manganese-based material and that of Example 1 is that ethanol is used instead of ethylene glycol.

[0097] Example 11

[0098] This disclosure provides a lithium iron phosphate coated lithium-rich manganese-based material. The only difference between the lithium iron phosphate coated lithium-rich manganese-based material and Example 1 is that the amount of LiOH·H2O and H3PO4 added is changed, so that the molar ratio of lithium in LiOH·H2O, iron in FeSO4·7H2O and phosphorus in H3PO4 is: Li:Fe:P = 0.8:1:0.8.

[0099] Example 12

[0100] This disclosure provides a lithium iron phosphate coated lithium-rich manganese-based material. The only difference between the lithium iron phosphate coated lithium-rich manganese-based material and Example 1 is that the amount of LiOH·H2O and H3PO4 added is changed, so that the molar ratio of lithium in LiOH·H2O, iron in FeSO4·7H2O and phosphorus in H3PO4 is: Li:Fe:P = 1.2:1:1.2.

[0101] Comparative Example 1

[0102] This disclosure provides a comparative example of a lithium iron phosphate-coated lithium-rich manganese-based material, the preparation method of which includes the following steps:

[0103] (1) Weigh out FeSO4·7H2O (1.67g, 6mmol), H3PO4 (0.59g, 6mmol), and 0.3g LNMO and dissolve them in 20mL of ethylene glycol to obtain the first mixed solution;

[0104] (2) Weigh out 0.25 g of LiOH·H2O and dissolve it in 15 mL of ethylene glycol to obtain a second mixed solution;

[0105] (3) The second mixed solution is added dropwise to the first mixed solution at a rate of 35 mL / h and stirred. After the addition is completed, the mixture is stirred for 1 h to obtain the third mixed solution. The molar ratio of lithium in LiOH·H2O, iron in FeSO4·7H2O and phosphorus in H3PO4 is: Li∶Fe∶P=1∶1∶1.

[0106] (4) The third mixed solution was transferred to a 100 mL reactor and reacted at 180 °C for 10 h. After the reaction was completed, the mixture was naturally cooled to room temperature, filtered, and the residue was collected. The residue was washed three times with deionized water and ethanol, respectively. After washing, it was vacuum dried at 70 °C for 3 h to obtain lithium iron phosphate coated lithium-rich manganese-based material precursor.

[0107] (5) The lithium iron phosphate coated lithium-rich manganese-based material precursor was ground and calcined at 500°C for 3 hours under an argon atmosphere to obtain lithium iron phosphate coated lithium-rich manganese-based material.

[0108] Comparative Example 2

[0109] This disclosure provides a lithium-rich manganese-based material as a comparative example, the preparation method of which includes the following steps:

[0110] (1) Weigh 0.3g of LNMO and dissolve it in 20mL of ethylene glycol to obtain the first mixed solution;

[0111] (2) Thioacetamide (0.009 g, 0.12 mmol) was added to the first mixed solution (the mass ratio of thioacetamide to LNMO is 3 wt%). After the addition was complete, the solution was transferred to a 100 mL reactor and reacted at 180 °C for 10 h. After the reaction was completed, the solution was naturally cooled to room temperature, filtered, and the residue was collected. The residue was washed three times with deionized water and ethanol, respectively. After washing, the residue was vacuum dried at 70 °C for 3 h to obtain the lithium-rich manganese-based material precursor.

[0112] (3) Grind the lithium-rich manganese-based material precursor and calcine it at 500°C for 3 hours under an argon atmosphere to obtain the lithium-rich manganese-based material.

[0113] Comparative Example 3

[0114] This disclosure provides a lithium iron phosphate material as a comparative example, the preparation method of which includes the following steps:

[0115] (1) Weigh FeSO4·7H2O (1.67g, 6mmol) and H3PO4 (0.59g, 6mmol) and dissolve them in 20mL of ethylene glycol to obtain the first mixed solution;

[0116] (2) Weigh out 0.25 g of LiOH·H2O and dissolve it in 15 mL of ethylene glycol to obtain a second mixed solution;

[0117] (3) The second mixed solution is added dropwise to the first mixed solution at a rate of 35 mL / h and stirred. After the addition is completed, the mixture is stirred for 1 h to obtain the third mixed solution. The molar ratio of lithium in LiOH·H2O, iron in FeSO4·7H2O and phosphorus in H3PO4 is: Li∶Fe∶P=1∶1∶1.

[0118] (4) Add thioacetamide (0.009 g, 0.12 mmol) to the third mixed solution (the molar ratio of sulfur in thioacetamide to iron in the iron source is: S:Fe = 0.02:1); after the addition is complete, transfer the solution to a 100 mL reactor and react at 180 °C for 10 h; after the reaction is complete, cool naturally to room temperature, filter, collect the filter residue, wash with deionized water and ethanol three times respectively, and after washing, vacuum dry at 70 °C for 3 h to obtain lithium iron phosphate material precursor;

[0119] (5) Grind the lithium iron phosphate material precursor and calcine it at 500°C for 3 hours under an argon atmosphere to obtain lithium iron phosphate material.

[0120] Comparative Example 4

[0121] This disclosure provides a comparative example of a lithium iron phosphate-coated lithium-rich manganese-based material, the preparation method of which includes the following steps:

[0122] (1) Weigh out FeSO4·7H2O (1.67g, 6mmol), H3PO4 (0.59g, 6mmol), LiOH·H2O (0.25g, 6mmol), and 0.3g LNMO and dissolve them in 35mL of ethylene glycol. Stir for 1h to obtain the first mixed solution. The molar ratio of lithium in LiOH·H2O, iron in FeSO4·7H2O, and phosphorus in H3PO4 is: Li∶Fe∶P=1∶1∶1.

[0123] (2) Thioacetamide (0.009 g, 0.12 mmol) was added to the first mixed solution (the molar ratio of sulfur in thioacetamide to iron in the iron source was S:Fe = 0.02:1, and the mass ratio of thioacetamide to LNMO was 3 wt%). After the addition was complete, the solution was transferred to a 100 mL reactor and reacted at 180 °C for 10 h. After the reaction was completed, the solution was naturally cooled to room temperature, filtered, and the residue was collected. The residue was washed three times with deionized water and ethanol, respectively. After washing, the residue was vacuum dried at 70 °C for 3 h to obtain the lithium iron phosphate coated lithium-rich manganese-based material precursor.

[0124] (3) The lithium iron phosphate coated lithium-rich manganese-based material precursor was ground and calcined at 500°C for 3 hours under an argon atmosphere to obtain lithium iron phosphate coated lithium-rich manganese-based material.

[0125] Comparative Example 5

[0126] This disclosure provides a comparative example of a lithium iron phosphate-coated lithium-rich manganese-based material, the preparation method of which includes the following steps:

[0127] (1) Weigh FeSO4·7H2O (1.67g, 6mmol), H3PO4 (0.59g, 6mmol), 0.3g LNMO, LiOH·H2O (0.25g, 6mmol), and thioacetamide (0.009g, 0.12mmol) and dissolve them in 35mL of ethylene glycol to obtain the first mixed solution;

[0128] (2) The first mixed solution was transferred to a 100 mL reactor and reacted at 180 °C for 10 h. After the reaction was completed, the mixture was naturally cooled to room temperature, filtered, and the residue was collected. The residue was washed three times with deionized water and ethanol, respectively. After washing, it was vacuum dried at 70 °C for 3 h to obtain lithium iron phosphate coated lithium-rich manganese-based material precursor.

[0129] (3) The lithium iron phosphate coated lithium-rich manganese-based material precursor was ground and calcined at 500°C for 3 hours under an argon atmosphere to obtain lithium iron phosphate coated lithium-rich manganese-based material.

[0130] Example of effect

[0131] This disclosure verifies the performance of the materials prepared in Examples 1-12 and Comparative Examples 1-5. The prepared materials were then used to construct coin cells for lithium-ion battery electrochemical performance testing. The specific steps were as follows: the prepared materials, conductive agent acetylene black, and adhesive polyvinylidene fluoride were uniformly mixed in N-methylpyrrolidone at a ratio of 90:5:5. This mixture was then coated onto aluminum foil and dried in a vacuum drying oven. After drying, the cells were assembled in an argon glove box and pressed into positive electrode sheets using a tablet press. The negative electrode was a lithium metal sheet. The electrolyte was 1M LiPF6-EC:DMC (EC:DMC volume ratio EC:DMC = 1:1), and a polypropylene porous membrane was used as the separator. The electrochemical performance was tested, and the results are shown in Table 1.

[0132] Table 1

[0133]

[0134]

[0135] As can be seen from Table 1, when the preparation method of this disclosure is used, the resulting material is applied to the preparation of lithium-ion batteries, and the resulting lithium-ion batteries have excellent cycle performance and rate performance, with an initial efficiency of over 93.2%, a 0.1C discharge capacity of over 229.4 mAh / g, and a 3C discharge capacity of over 128.5 mAh / g.

[0136] As can be seen from Examples 1-6, when preparing lithium iron phosphate coated lithium-rich manganese-based materials, the molar ratio of sulfur in thioacetamide and iron in the iron source significantly affects the overall performance of lithium ions. When the molar ratio of the two is further selected within the range of this disclosure, the cycle performance and rate performance of the obtained lithium ions are more excellent. Specifically, the first efficiency is above 95.2%, the 0.1C discharge capacity is above 236.9 mAh / g, and the 3C discharge capacity is above 131.1 mAh / g.

[0137] As can be seen from Examples 1 and 7-9, the mass ratio of thioacetamide to LNMO also affects the performance of the product. When the mass ratio of the two is further selected within the scope of this disclosure, the cycle performance and rate performance of the lithium ions are more excellent. Specifically, the first efficiency is above 96.5%, the 0.1C discharge capacity is above 251.6 mAh / g, and the 3C discharge capacity is above 140.9 mAh / g.

[0138] As can be seen from Examples 1 and 10, and Examples 1 and 11-12, the choice of organic solvent and the molar ratio of lithium in the lithium source, iron in the iron source and phosphorus in the phosphorus source can also affect the performance of lithium ions to a certain extent.

[0139] As can be seen from Example 1 and Comparative Example 1, when thioacetamide is not introduced during the preparation process, the resulting lithium-ion battery exhibits a significant decrease in both cycle performance and rate performance when applied to the preparation of lithium-ion batteries. As can be seen from Example 1 and Comparative Examples 2-3, when the outer layer is not coated with lithium iron phosphate or the inner layer does not contain lithium-rich manganese-based material, the overall performance of the corresponding lithium-ion batteries exhibits a significant decrease. As can be seen from Example 1 and Comparative Examples 4-5, when the addition method described in this disclosure is not adopted, the overall performance of the corresponding lithium-ion batteries decreases significantly.

Claims

1. A method for preparing lithium iron phosphate coated lithium-rich manganese-based materials, characterized in that, The preparation method includes the following steps: Iron source, phosphorus source and lithium-rich manganese-based material are dissolved in a first organic solvent to obtain a first mixed solution; The lithium source is dissolved in the second organic solvent to obtain the second mixed solution; The second mixed solution is added dropwise to the first mixed solution and stirred to obtain the third mixed solution; Thioacetamide was added to the third mixed solution and heated to react. After the reaction was completed, the solution was cooled, filtered, and the filter residue was collected, washed, and dried to obtain a lithium iron phosphate-coated lithium-rich manganese-based material precursor. The lithium iron phosphate-coated lithium-rich manganese-based material precursor was ground and then calcined to obtain the lithium iron phosphate-coated lithium-rich manganese-based material. The mass ratio of the thioacetamide to the lithium-rich manganese-based material is (0.02-0.04):1; The molar ratio of sulfur in the thioacetamide to iron in the iron source is (0.02-0.3):

1.

2. The preparation method according to claim 1, characterized in that, The molar ratio of iron in the iron source, phosphorus in the phosphorus source, and lithium in the lithium source is 1:1:

1.

3. The preparation method according to claim 1, characterized in that, In the first mixed solution, the mass concentration of the solute is (0.08-0.18) g / mL; And / or, in the second mixed solution, the mass concentration of the solute is (0.008-0.028) g / mL.

4. The preparation method according to claim 1, characterized in that, At least one of the following (a)-(e): (a) The iron source is selected from at least one of ferrous phosphate, ferrous oxalate, ferrous sulfate or ferrous chloride; (b) The phosphorus source is selected from at least one of ammonium dihydrogen phosphate, ammonium phosphate, diammonium hydrogen phosphate, and potassium dihydrogen phosphate; (c) The lithium source is selected from at least one of lithium carbonate, lithium hydroxide or lithium acetate; (d) The first organic solvent and the second organic solvent are each independently selected from at least one of ethylene glycol, glycerol, or ethanol; (e) The structural formula of the lithium-rich manganese-based material is xLi2MnO3·(1-x)LiNiO2, where 0.3 < x < 1.

5. The preparation method according to claim 1, characterized in that, The stirring time is 0.5-1.5 hours; And / or, the temperature of the heating reaction is 150-210°C, and the heating reaction time is 8-12 hours; And / or, the calcination temperature is 450-550℃, and the calcination time is 2.5-3.5h.

6. A lithium iron phosphate-coated lithium-rich manganese-based material, characterized in that, The lithium iron phosphate-coated lithium-rich manganese-based material is prepared by the preparation method described in any one of claims 1-5.

7. The application of lithium iron phosphate coated lithium-rich manganese-based material as described in claim 6 in the preparation of cathode materials.

8. A lithium-ion battery, comprising a positive electrode, a negative electrode, and an electrolyte, characterized in that, The positive electrode comprises lithium iron phosphate coated with lithium-rich manganese-based material as described in claim 6.

Citation Information

Patent Citations

  • Lithium iron phosphate-coated lithium-rich positive electrode material and preparation method thereof

    CN107968195A

  • Surface modified high-nickel ternary positive electrode material and modification method thereof, and lithium ion battery

    CN109994712A